Revision of Failed Sacroiliac Joint Posterior Interpositional Structural Allograft Stabilization with Lateral Porous Titanium Implants: A Multicenter Case Series [Response to Letter] - Kranenburg A; Garcia-Diaz G; Cook JH; Thambuswamy M; James W; Stevens D; Bruggeman A; Chen Y; Capobianco R; Reckling WC; Siegal JD (Medical Devices: Evidence and Research, 2022)
Andy Kranenburg,1 Gabriel Garcia-Diaz,2 Judson H Cook,3 Michael Thambuswamy,4 Whitney James,5 David Stevens,6 Adam Bruggeman,7 Ying Chen,8 Robyn Capobianco,9 W Carlton Reckling,9 Joel D Siegal10 1Southern Oregon Orthopedics, Medford, OR, USA; 2OrthoSpine Advance Health, Inc, Merced, CA, USA; 3Central Texas Brain and Spine, Austin, TX, USA; 4Oklahoma Spine & Brain Institute, Tulsa, OK, USA; 5James Marco Health, Prescott, AZ, USA; 6Utah Spine Specialists, Bountiful, UT, USA; 7Texas Spine Care Center, San Antonio, TX, USA; 8OrthoNeuro Inc, New Albany, OH, USA; 9SI-BONE Inc, Santa Clara, CA, USA; 10Key Clinics LLC, Mayfield Heights, OH, USACorrespondence: Andy Kranenburg, Tel +1 541-864-0263, Email andy.kranenburg@gmail.com